Acupuncture for pain and pain-related disability in deep infiltrating endometriosis - Chiarle, Giulia; Allais, Gianni; Sinigaglia, Silvia; Airola, Gisella; Rolando, Sara; Bergandi, Fabiola; Micalef, Salvatore; Benedetto, Chiara (Frontiers in Pain Research, 2024)
OBJECTIVES: To evaluate the efficacy of acupuncture in relieving symptoms (dysmenorrhea, dyspareunia, pelvic pain and dyschezia) intensity, improving functional disability, reducing the number of days per months of dysmenorrhea, the frequency and the efficacy of analgesic use in deep infiltrating endometriosis (DIE). The safety profile was also evaluated. METHODS: The study sample was 34 patients with DIE; for 2 months (T-2, T-1) the women recorded diary notes on the numbers of days of menstruation, the presence, intensity, and disability related to dysmenorrhea, dyspareunia, pelvic pain, and dyschezia. They then received a total of 15 acupuncture treatments over 6 months (T1-T6; once a week for 12 weeks, then once a month for 3 months). RESULTS: Dysmenorrhea intensity was decreased during treatment. A decrease of at least 50% in number of days of dysmenorrhea, and a decrease in moderate-to-severe disability starting from T1 to T6 was recorded for 58.6% of patients. Dyspareunia intensity steadily decreased starting at T2; the percentage of women with moderate-to-severe disability declined from 73.3% at T-2, to 36.9% at T3, T4, and T5. A decrease in pelvic pain score was noted starting at T1; the percentage of disability decreased from 83.3% at T-2 to 33.3% at T3 and T6. The intensity of dyschezia decreased from T-2 to T3 and T4 and then increased slightly. Analgesic drug use was lower during treatment and its efficacy appeared to be greater. CONCLUSIONS: The limitations notwithstanding our study-findings show that acupuncture was safe and effective in reducing pain intensity and symptoms-related disability. Larger-scale studies are needed to compare acupuncture and pharmacotherapy for endometriosis-related pain.